Morning Glory Disc Anomaly, A Report of a Successfully Treated Case of Functional Amblyopia - Cavazos Adame, Humberto (2015)
Morning Glory Disc Anomaly (MGDA) is a congenital malformation of the optic nerve characterized by the presence of a funnel-shaped macropapilla with neuroglial remnants in its center surrounded by an elevated and pigmented chorioretinal ring. Its incidence is rare and no gender predisposition has been found. Associated conditions like strabismus lead to an early diagnosis. We report the case of a 3.8-year-old boy with amblyopia of the right eye (count fingers 0.3 meters) due to MGDA. Correction of the refractive error with glasses, along with occlusive therapy resulted in a visual acuity of 20/100 after a five-year follow up. The presence of amblyopia in these cases demands an early management oriented to improve the visual acuity. Every patient with an anatomical malformation diagnosed during the period of sensory maturation should be treated with occlusive therapy and followed on a regular basis to diagnose associated conditions such as retinal detachment. We recommend occlusive therapy in every patient diagnosed with MGDA or in any patient with unilateral or asymmetric structural abnormalities that could lead to amblyopia. This 5-year case follow-up provides additional evidence of the importance of treatment during the period of amblyopia reversibility